After the Prosperous Age : State and Elites in Early Nineteenth Century Suzhou - Han, Seunghyun, 1970- (Book collections on Project MUSE., 2016)
"By analyzing the social and cultural interplay between state power and local elites of Suzhou, a city renowned for its economic prosperity and local pride, from the eighteenth to the early nineteenth century, this illuminates the significance of this period in the reformulation of state-elite relations marked by elite public activism and the dissolution of centralized cultural order"--Provided by publisher